Design and Synthesis of Caged Thiols for Development of Photo-Activatable Peptides, Inhibitors and Biomaterials - Mahmoodi, Mohammad Mohsen (My University, 2017)
The ability of light to traverse various chemical and biological barriers and be modulated by time and amplitude makes light- regulated molecules unique tools for a plethora of applications in the areas of chemistry and biology and biomaterials. Photo-removable protecting groups, also known as caging groups, are one of the most important light-regulated tools, which can be utilized to mask specific functional groups in molecules such that they can be cleaved on demand upon irradiation. In biological applications, this typically involves masking a biomolecule with a caging group to produce a compound whose biological activity is either increased or decreased upon uncaging. The recent development of two-photon-sensitive protecting groups, which allow uncaging using near-infrared (near-IR) irradiation, has resulted in significant improvements in the spatiotemporal resolution of uncaging as well as increased penetration with lower photo-toxicity; the latter attribute is of particular importance for the use of caged molecules in tissue samples or intact organisms that are essentially opaque to UV light. Additionally, two-photon un- caging approaches have proved to be extremely useful for creating novel biomaterials; in that strategy, laser irradiation is used to unmask a specific caged functionality pre-incorporated into a hydrogel or matrix, such that it can be used to immobilize peptides, proteins or cells in a three dimensionally controlled fashion. In this work, we analyzed the photolysis of several Bhc-protected thiol-containing peptides and small molecules. Those experiments revealed that Bhc-caged thiols exhibit variable uncaging yields and that their photolysis frequently leads to the formation of an unwanted rearrangement product. To circumvent this problem, we explored and designed two alternative highly efficient thiol caging groups that can be uncaged upon one- and two-photon irradiation. we initially explored using nitrodibenzofuran (NDBF) as a thiol caging group. Cysteine-containing peptides were prepared where the thiol was protected with an NDBF group. To probe the utility of this protecting group for biological experiments, thiol group uncaging was carried out using a K-Ras-derived peptide containing an NDBF-protected cysteine. Irradiation of that molecule in the presence of protein farnesyltransferase (PFTase) and farnesyl diphosphate (FPP) resulted in the formation of the free thiol form and subsequent enzymatic conversion to a prenylated species. In order to illustrate the utility of this strategy for the development of caged peptides that can be activated via irradiation inside live cells, the thiol of a cell-penetrating peptide known to be a substrate for palmitoyl acyltransferase was protected as a NDBF thioether. Irradiation of human ovarian carcinoma (SKOV3) cells, preincubated with the probe, resulted in migration of the peptide from the cytosol/Golgi to the plasma membrane (visualized via confocal microscopy) due to enzymatic palmitoylation. These data suggest that the NDBF group should be useful for caging thiols in peptides and potentially larger proteins assembled via native chemical ligation for biological applications. As another approach, guided by mechanistic studies of the photo-triggered isomerization of Bhc-thiols, we developed 6-bromo-7- hydroxy-3-methylcoumarin-4-ylmethyl (mBhc) as an alternative coumarin-based caging group that can afford efficient thiol release upon one- and two-photon irradiation. To test the efficiency of mBhc for thiol-protection in peptides, we have synthesized a K-Ras-derived peptide where the thiol was protected by mBhc. One- and two-photon photolysis of the caged peptide resulted in clean conversion to the free compound with no photo-isomerization. Irradiation of the caged peptide using a near-IR laser in the presence of an enzyme (protein farnesyltransferase, PFTase) resulted in the generation of a free thiol-containing peptide which was then enzymatically farnesylated. To further evaluate the utility of this novel caging group for biomaterial applications, an mBhc-protected thiol was covalently incorporated into a hydrogel. Using a 740 nm two- photon laser from a confocal microscope, patterns of free thiols were generated inside the matrix and visualized by reaction with maleimide functionalized fluorophores. Such 3D patterns could be useful for a variety of applications in tissue engineering. Such highly tuned matrices allow artificial extracellular environments to be created that can be used to study cell migration, differentiation and cell–cell interactions. Lastly, we strived to develop a novel NDBF-based caging group with red-shifted absorption maxima and improved two-photon uncaging efficiency. Inspired by previous studies, we elected to modify the structure of NDBF by adding an amine as a donor group, to generate a donor-acceptor system. Hence, 2-bromo-2-(7-(dimethylamino)-3-nitrodibenzofuran-2-yl)acetate was synthesized in 9-steps. Initial analysis of spectral properties of the designed molecule showed the absorption maxima (λmax) to be 440 nm. This is110 nm red-shifted relative to λmax of NDBF. The uncaging efficiency of this novel protecting group remains to be tested.
University of Minnesota Ph.D. dissertation. JUne 2017. Major: Chemistry. Advisor: Mark Distefano. 1 computer file (PDF); xv, 134 pages.
Keywords: Peptide; Photo-cleavable protecting groups; Photo-patterning; Ras signaling; Thiols; Two-photon